The Effect of Job Crafting on Work Engagement on Working Students - Awaliya Febby Ariyanti; Tantri Yanuar Rahmat Syah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
One of the main factors that are of concern to business people is the work engagement of each employee. The high work engagement of employees can add various benefits to the organization, because with high work engagement, employees will voluntarily give their best contribution to their work, and this will lead to the company's success. Currently, there are many students who are also working. Generally, students have views and ways of working that are different from ordinary employees. This is what business people need to consider in order to make the best strategy to maximize the productivity of working student. Based on this description, the purpose of this study is to determine whether job crafting, work meaning, and psychological capital can affect work engagement in working students. This study was conducted to update the concept of the previous research model by Letona-Ibañez et al. (2021) regarding work engagement, by adding psychological capital as the dependent variable. This study uses the Structural Equation Model (SEM) with a total sample of 120 respondents who were determined using the purposive sampling method. The result of this research is that job crafting has a positive effect on work meaning and work engagement. Work meaning has a positive effect on work engagement. Work meaning mediates the relationship between job crafting and work engagement. Psychological capital does not have a positive effect on work engagement. For working students, work engagement can be strengthened by increasing their job crafting and work meaning.